Literacy and the Girl-Child Empowerment for Sustainable Development: A Study of Amma Darko’s Faceless - Egbung, Itang Ede; Owan, Jayne (Mediterranean Journal of Social Sciences, 2019)
This paper examines literacy as a veritable tool towards the empowerment of the girl-child that leads to sustainable development in the family in particular and the larger society. Literacy is the ability to read and write; formal education is the avenue through which this can be achieved. Education is an investment that when properly utilized can empower, liberate and embolden; on the other hand, the lack of education exposes one to exploitation, oppression, ignorance and poverty. Using Amma Darko’s Faceless, this paper discovers that the girl-child who lacks education is exposed to the danger of poverty and prostitution, but through the intervention of a group of educated women in MUTE; hope and a bright future is given to the vulnerable girl-child. Applying the feminist theory that advocates for the freedom and self-assertion of the female gender from ignorance, oppression and exploitation; this paper concludes that the rehabilitation of the street girl-child by the literate women empowers her to be a source of livelihood for her family, thereby sustaining economic development and reducing petty crime rate in the society which is prevalent among the youths due to illiteracy.